2019
DOI: 10.1186/s13550-019-0544-3
|View full text |Cite
|
Sign up to set email alerts
|

Parathyroid imaging with 18F-fluorocholine PET/CT as a first-line imaging modality in primary hyperparathyroidism: a retrospective cohort study

Abstract: Background 18 F-fluorocholine (FCH) PET/CT is a promising technique for visualizing hyperfunctioning parathyroid glands in hyperparathyroidism. It is still under debate whether to use this technique as a first-line imaging modality or to use it when conventional techniques such as 99m Tc-sestamibi scintigraphy or ultrasonography are inconclusive. This study evaluates FCH PET/CT as a first-line modality. Methods Patients with pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
38
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(46 citation statements)
references
References 26 publications
3
38
0
5
Order By: Relevance
“…Recent studies and the results of our phase II study APACH1 concordantly suggest the superiority of F18-choline (FCH) PET/CT for PTA localization [ 5 , 11 13 ]. In the APACH1 study [ 12 ], 25 patients with PHPT and negative or inconclusive MIBI SPECT/CT results underwent FCH PET/CT, resulting in 22 FCH PET/CT guided surgeries: 17 MIPs, 1 bilateral cervical exploration for multifocality and 4 other surgical procedures.…”
Section: Introductionsupporting
confidence: 54%
“…Recent studies and the results of our phase II study APACH1 concordantly suggest the superiority of F18-choline (FCH) PET/CT for PTA localization [ 5 , 11 13 ]. In the APACH1 study [ 12 ], 25 patients with PHPT and negative or inconclusive MIBI SPECT/CT results underwent FCH PET/CT, resulting in 22 FCH PET/CT guided surgeries: 17 MIPs, 1 bilateral cervical exploration for multifocality and 4 other surgical procedures.…”
Section: Introductionsupporting
confidence: 54%
“…Negative localization studies make surgical treatment difficult. In both the selected articles in our meta-analysis and in previous meta-analysis, CH localization studies have shown greater ability to locate pathological glands [34,[42][43][44][45] than MIBI or methionine [46][47][48] in both first exploration and rescue scan [31,49]. The probability of uptake with CH is above 0.9 on both first scans and scans performed after negative MIBI study (in these cases the combination of both techniques reaches a prevalence of uptake of 0.97).…”
Section: Discussionmentioning
confidence: 70%
“…Recently, 18 F-fluorocholine positron emission tomography/computed tomography (FCH-PET/CT) has shown superior sensitivity in localizing parathyroid adenomas than conventional morphological and functional imaging [ 15 18 ]. FCH-PET/CT has been recommended when conventional imaging is negative or discordant [ 19 24 ] and also as first line imaging [ 25 ]. However, FCH-PET/CT specificity for parathyroid tissue (vs. other neck tissues) and its sensitivity in visualising hyperplastic parathyroid glands of FHH that are usually smaller than parathyroid adenomas, are not well known.…”
Section: Introductionmentioning
confidence: 99%